2010
DOI: 10.1177/0738894210366510
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the Magnitude of Civilization Conflict

Abstract: Multiple studies of Huntington's suggestion of a clash of civilizations have found no support for it. This study does not reanalyze his thesis, but rather focuses on specific features of the different-civilization conflict he theorizes about. Using empirical analysis I find that different-civilization conflict is more prevalent than same-civilization conflict, and is therefore appropriate for continued scholarly examination. Even so, I conclude that over time it is not only shrinking as a percentage of the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…The scholarly consensus at present is that there is a strong bivariate relationship between Islam and democracy and also Islam and political violence, but in each case, the relationship weakens substantially when controlling for potential covariates. In general, prior research provides some evidence that religious and civilizational clashes are associated with greater conflict intensity (Ellingsen 2005; Ellis 2010; Pearce 2005), and at least one recent study found evidence that they may be associated with conflict onset (Charron 2010). However, most of the work on religion and contentious action has focused on the role of religious actors in civil war (Basedau, Pfeiffer, and Vüllers 2016; Fox 2004; Hassner 2011; Svensson 2007).…”
Section: Religion Civic Engagement and Political Violencementioning
confidence: 99%
“…The scholarly consensus at present is that there is a strong bivariate relationship between Islam and democracy and also Islam and political violence, but in each case, the relationship weakens substantially when controlling for potential covariates. In general, prior research provides some evidence that religious and civilizational clashes are associated with greater conflict intensity (Ellingsen 2005; Ellis 2010; Pearce 2005), and at least one recent study found evidence that they may be associated with conflict onset (Charron 2010). However, most of the work on religion and contentious action has focused on the role of religious actors in civil war (Basedau, Pfeiffer, and Vüllers 2016; Fox 2004; Hassner 2011; Svensson 2007).…”
Section: Religion Civic Engagement and Political Violencementioning
confidence: 99%
“…We also argue that religion shapes recognition decisions through transnational mechanisms. Countries that share a dominant religious identity may tend to support one another in international relations, all else equal (Sandal and Fox 2004; Ellis 2010). Religious affinity has also been shown to affect international involvement in civil wars (Carment, James, and Taydas 2006).…”
Section: Religion and Recognition: Domestic And Transnational Mechanismsmentioning
confidence: 99%
“…It is probably true, then, that students of East Asia IR take the role of civilizational narratives in IR more seriously than transatlantic IR theory does (with a few exceptions, notably Huntington) (Ellis 2010). This is not Huntington redux, mainly because these civilizational identities are not essentialized but recognized as complex, malleable, constructed phenomena to be explained (Katzenstein 2010(Katzenstein , 2012b.…”
Section: Structural Theories Of Conflict and International Ordersmentioning
confidence: 99%